Deskripsi Kreativitas Pemecahan Masalah Matematika Ditinjau dari Pemahaman Konsep Siswa Kelas VIII - Irma Magfirah; Andi Andong (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2022)
The research aimed to describe: (1) Mathematics problem solving creativities based on Mathematics concept understandings of class VIII students at MTs Al-Fakhriyah Makassar; (2) the difference of Mathematics problem solving creativities based on Mathematics concept understandings of class VIII students at MTs Al-Fakhriyah Makassar. The research was desctiptive research with qualitative approach. The subjects of te research were 3 students with the assumptions that 1 student with hight concept understanding, 1 student with medium concept understanding, and 1 student low hight concept understanding who were obtained from class VIII in MTs Al-Fakhriyah Makassar. The instrumens of the research were the research herself as the main instrument and concept understanding test, creativity test, and interview quideline as supporting instruments. The data were collected by using triangulation technique. The data were analyzed by conducting several stages, namely: (1) analyzing all data which were available from various sources; (2) data reduction; (3) data presentation; (4) making coding; (5) data presentation; and (6) drawing conclusing. The results of the research showed that: (1) the subjects with high, medium, and low concept understanding ability through all the thinking process from the preparation stage, incibation, illumination, and verification stage; (2) there were differences of Mathematics problem solving creativities between the subjects with high, medium, and low concept understanding ability where the subjects with high and medium concept understanding abilities discovered their ideas not triggered by the condition of their surroundings of developed their ideas to build new way in solving Mathematis understanding Creativity Test; whereas, the subject with low concept understanding ability discovered the idea through subconscious in incubation stage. Basides, the difference of the three subjects also due to the approach done by the three subjects in verifying their ideas.